Spinal brucellosis. 4 years of experience. - Lopes, C (1992)
The Authors retrospectively studied 17 patients who have been admitted to the Infectious Diseases Clinic of Coimbra University Hospital during a four year period and whose final diagnosis was brucellar spondylitis. Clinical, epidemiological, laboratory and imaging features are analyzed, as well as those related to the therapeutic schedules and outcome. Females were more often affected (70.58%) and the mean age was 53.35 +/- 13.82 years. Lumbar spine was most frequently involved and an unusual elevated incidence of paravertebral soft tissue swelling was noticed (23.52%). Two patients were also suffering from neurobrucellosis (11.76%). The preferred therapeutic schedule was rifampin and doxycycline and surgery was performed in one patient. Finally, several comments are made regarding basically the incidence, laboratory and imaging diagnosis, therapeutic aspects and evolution of the disease. The imaging similarities and differences between tuberculous, pyogenic and brucellar spondylitis are briefly approached.